DSM-5: Overview of methodological procedure - Jović, Vladimir M. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
Contemporary classifications of mental disorders were used to bring back psychiatry and psychopathology to the biomedical model. After more than thirty years, syndromal approach to nozography is called into question regarding it’s philosophical and methodological aspects. The aim of this paper is to present an overview of the methodological approach in the creation of classification of mental disorders since DSM-III, over a several principles: first of all it is proclaimed "atheoretical approach" to classification, which is applied during creation of so-called "operationalized" criteria for disorders, followed with "nomothetic approach", which was presented as the only legitimate means to draw conclusions about mental disorders. The outcome of this methodological procedure can be followed through its outcomes: measures of reliability and validity of nosological categories, as well as issue of psychiatric co-morbidity, which can be seen as an artefact of the methodological process.
Keywords: Biomedical Model; psychiatric nozology; mental disorders; DSM-5